Efficiency drivers of insurers in GCC: An analysis incorporating company-specific and external environmental variables - Rohit Bansal; Dharmendra Singh (Cogent Economics & Finance, 2021)
The study aims to a comprehensive measure of listed insurance companies' technical efficiency in GCC countries and benchmarking, peer count summary, and measuring productivity changes in the first stage. In the second stage, the technical efficiency, pure technical efficiency, and scale efficiency scores have been regressed with internal (company variables) and external environmental variables. This paper first examines financial freedom and reinsurance activities on 60 insurers' efficiency from all GCC countries during 2016-2019. The results suggest a positive impact of economic freedom, solvency on technical efficiency components, and the negative effect of reinsurance ceding, market concentration on GCC insurers' technical efficiency. In productivity changes, UAE companies are doing well as compared to other countries' insurers. Overall, GCC insurers' efficiency is improving with pure technical efficiency having a CAGR of 2.13% and scale efficiency a CAGR of 2.96%. Based on the peer count summary, only the UAE and Saudi Arabia's companies can be benchmarked against another insurance company. Also, this research is one of the most comprehensive ones in the GCC region; this is the first study on an extensive data set to the best of our knowledge, including conventional insurers operating across GCC countries. This study is based on 60 insurers listed on the stock exchanges of six GCC countries. This will also be the first empirical evidence on the GCC insurers, which measures the impact of company-specific variables and unique environmental variables separately on the two components of technical efficiency using Tobit regression. The positive association of competition and financial freedom with technical efficiency may encourage regulators and policymakers to ensure less government intervention and give more support and freedom for a better competitive insurance industry.
Keywords: 330; DEA; Efficiency; GCC; peer-count summary; Tobit regression